Intranasal inoculations of naked or PLGA-PEI nanovectored DNA vaccine induce systemic and mucosal antibodies in pigs: A feasibility study. (October 2020) - Souci, Laurent; Jaunet, Hervé; Le Diguerher, Gérald; Guionnet, Jean-Marie; Béven, Véronique; Paboeuf, Frédéric; Montier, Tristan; Dory, Daniel
Abstract: Mucosa are the routes of entry of most pathogens into animals' organisms. Reducing the important global burden of mucosal infectious diseases in livestock animals is required in the field of veterinary public health. For veterinary respiratory pathogens, one possible strategy is the development of intranasal (IN) DNA vaccination. The aim of this study was to assess the feasibility of IN DNA vaccination in pigs, an important species in livestock production industry, and a source of zoonotic diseases. To achieve this goal, we used a DNA vaccine against pseudorabies virus (PrV) encoding the immunogenic glycoprotein B (pcDNA3-gB plasmid). When pigs were inoculated with the naked DNA vaccine through the IN route, PrV-specific IgG and IgA type antibodies were detected in porcine sera. Interestingly, mucosal salivary IgA antibodies against PrV were also detected, at similar levels to those measured following intramuscular injection (positive controls). Furthermore, the IN delivery of pcDNA3-gB combined with PLGA-PEI nanoparticles resulted in similar levels of antibodies but was associated with an increase in the duration of detection of mucosal IgA for 2 out of 3 pigs. Our results suggest that there is room to improve the efficacy of IN DNA vaccination in pigs through optimization of IN inoculations, for example by using nanoparticles such as PLGA-PEI. Further studies will be dedicated to optimizing and testing the protective potential of IN DNA vaccination procedures against PrV. Highlights: Intranasal DNA vaccination study in pigs. Pseudorabies glycoprotein B used as an immunogenic antigen. Naked DNA vaccine induces systemic and local immune responses. Association of the DNA vaccine with PLGA-PEI seems to extend the duration of detection of mucosal IgA for 2 out of 3 pigs. Proof of concept study: future optimizations are required.